Coconut shell biochar with ultrahigh specific surface area as well as preparation method and application of coconut shell biochar

The ultra-high specific surface area coconut shell biochar is prepared by urea hydrothermal and KOH activation treatment, which solves the problems of insufficient adsorption performance and high cost of biochar in the prior art, and achieves the effect of efficient adsorption of radioactive gaseous iodine.

CN119191293APending Publication Date: 2024-12-27SHANXI ZHEJIANG UNIVERSITY NEW MATERIALS & CHEMICAL RESEARCH INSTITUTE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411342108.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing biochar materials have insufficient performance in adsorbing radioactive gaseous iodine, and are costly, potentially toxic, making it difficult to quickly treat radioactive nuclear waste.

Method used

Urea hydrothermal and KOH activation treatment of coconut shells was used to prepare ultra-high specific surface area coconut shell biochar, forming a graded porous structure, significantly improving the adsorption performance of gaseous iodine.

Benefits of technology

It has achieved efficient adsorption of radioactive gaseous iodine in a short period of time, which has reduced material costs and improved the economic value of coconut shells, significantly improved the adsorption performance, and solved the problems of low adsorption amount and high cost in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191293A_ABST
    Figure CN119191293A_ABST
Patent Text Reader

Abstract

The invention provides coconut shell biochar with an ultrahigh specific surface area as well as a preparation method and application thereof, and relates to the technical field of biochar materials. The preparation method comprises the following steps: cleaning, drying, crushing and sieving coconut shells to obtain coconut shell powder; adding the coconut shell powder into a high-pressure reaction kettle, mixing with urea, performing hydrothermal reaction, and drying to obtain a hydrothermal product for later use; mixing the hydrothermal product with KOH through ball milling, placing the mixture in a tubular furnace, and carrying out heating carbonization under the protection of an inert atmosphere to obtain a carbonized product; and washing and drying the carbonized product to obtain the coconut shell biochar with the ultrahigh specific surface area. The coconut shell activated carbon prepared by the invention has a graded porous structure, the adsorption capacity of gaseous iodine at 75 DEG C within 3 hours reaches 6635mg / g, the problems of low adsorption capacity, overhigh cost of novel materials and potential toxicity of the existing carbon-based adsorbent are effectively solved, and radioactive gaseous iodine is efficiently treated while solid waste recycling is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biochar materials, and in particular to coconut shell biochar with ultra-high specific surface area and a preparation method and application thereof. Background Art

[0002] As global energy demand grows, pollution and resource depletion issues associated with limited fossil fuels are becoming increasingly prominent. Nuclear energy can be considered a viable alternative to fossil fuels due to its high energy density and the fact that it does not emit substances such as sulfur and nitrogen compounds or carbon dioxide. However, the development of nuclear energy has been hampered by the threat to the environment and human health posed by the disposal of radioactive nuclear waste and spent nuclear fuel. Among them, radioactive gaseous iodine (such as 129I) is an important volatile pollutant produced during the reprocessing of spent fuel. Due to its extremely long half-life (15.7 million years) and its ability to migrate rapidly in the atmosphere, water, and soil, it is considered one of the most harmful radionuclides to human health.

[0003] Among the commonly used iodine adsorbents, silver-impregnated materials are limited by their high cost and challenges in large-scale promotion in the short term. The synthesis of porous organic polymer (POP) materials is challenging, and the adsorption equilibrium time is long, which is not suitable for rapid treatment in emergency situations. Porous carbon materials are cost-effective and can precisely control the pore structure. By optimizing these structures, the rapid penetration of gaseous iodine can be promoted, thereby accelerating the time to reach adsorption equilibrium. Therefore, porous carbon materials are expected to become candidate materials for gaseous iodine adsorption. Among them, the use of agricultural waste to prepare biochar not only has a rich source of raw materials, but also contains a certain amount of organic functional groups in the biomass, which can create more adsorption sites. This method solves the problem of waste utilization and provides an economically feasible and environmentally friendly solution for the adsorption of radioactive gaseous iodine. The adsorption performance of biochar can be improved by activation methods, thereby increasing its surface area and optimizing its porosity. Among them, Tang et al. [Separation and Purification Technology, 2024, 335: 126214] used a dual activator and a new in-situ etching method based on polytetrafluoroethylene (PTFE) to prepare biochar from sewage sludge. The specific surface area of ​​modified biochar increased from 301m 2 / g increased to 1103m 2 / g, and the adsorption capacity for gaseous iodine was significantly improved to 2086mg / g. Wang et al. [Chemical Engineering Journal, 2023, 465: 143069] improved the chemical adsorption capacity of rice husk biochar by doping bismuth, increasing its adsorption capacity from 914mg / g to 1334mg / g. Yang et al. [Chemical Engineering Journal, 2023, 454: 140365] prepared porous biochar by zinc chloride activation of walnut shells and the adsorption capacity for gaseous iodine was 2374mg / g, which was 3.9 times higher than that of unactivated biochar. The improvement in adsorption capacity proves the positive effect of these modifications on the capture of gaseous iodine in biomass.

[0004] Despite the progress made in the adsorption of gaseous iodine by biochar materials, their performance is still significantly lower than that of recently reported porous organic polymers (POPs). Therefore, it is imperative to develop biochar materials with stronger adsorption capacity in a short period of time. Summary of the invention

[0005] The purpose of the present invention is to provide an ultra-high specific surface area coconut shell biochar and a preparation method thereof, and use the same as an adsorbent to adsorb radioactive gaseous iodine. The present invention is to use urea to hydrothermally and activate coconut shells with KOH to prepare ultra-high specific surface area coconut shell biochar. The coconut shell activated carbon prepared by the present invention has a hierarchical porous structure, and the adsorption of gaseous iodine reaches 6635 mg / g within 3 hours at 75°C, which effectively solves the problems of low adsorption capacity of existing carbon-based adsorbents, high cost of new materials, and potential toxicity, and efficiently treats radioactive gaseous iodine while realizing solid waste resource utilization.

[0006] The present invention is specifically implemented by adopting the following technical solutions:

[0007] A method for preparing ultra-high specific surface area coconut shell biochar comprises the following steps:

[0008] S1, washing, drying, crushing and sieving coconut shell to obtain coconut shell powder;

[0009] S2, adding the coconut shell powder into a high pressure reactor and mixing with urea, drying after hydrothermal reaction to obtain a hydrothermal product for standby use;

[0010] S3, mixing the hydrothermal product with KOH by ball milling, placing the mixture in a tube furnace, and carbonizing the mixture by heating under an inert atmosphere to obtain a carbonized product;

[0011] S4, washing and drying the carbonized product to obtain coconut shell biochar with ultra-high specific surface area.

[0012] Preferably, step S1 is to wash, dry, crush and sieve the coconut shell through a 100-200 mesh sieve.

[0013] Preferably, the mass ratio of the coconut shell powder to urea in step S2 is 1:1.5-3.

[0014] Preferably, the temperature of the hydrothermal reaction in step S2 is 200-250° C., and the time of the hydrothermal reaction is 1.5 h to 3 h.

[0015] Preferably, the mass ratio of the hydrothermal product to KOH in step S3 is 1:2-3.

[0016] Preferably, in step S3, the carbonization temperature is 800-1000° C., and the carbonization time is 1.5 h-3 h.

[0017] Preferably, the heating rate in step S3 is 3-8° C. / min.

[0018] Another object of the present invention is to provide a coconut shell biochar with ultra-high specific surface area. After testing, the specific surface area of ​​the coconut shell biochar of the present invention is 2900-3000m 2 / g, total pore volume is 2.1~2.3cm 3 / g, micropore volume is 1.1~1.2cm 3 The ultra-high specific surface area coconut shell biochar has an adsorption capacity of up to 6635 mg / g for gaseous elemental iodine, and the coconut shell biochar of the present invention has a strong iodine retention capacity, and the desorption rate at room temperature for 24 hours is 12.93%.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The coconut shell of the present invention has a wide source and low cost. The coconut shell is processed into a biochar material with an ultra-high specific surface area, which significantly increases the economic value of the coconut shell and reduces the processing cost of the biochar material;

[0021] (2) The present invention hydrothermally treats the mixture of coconut shell and urea, and then uses KOH for activation treatment, so that the prepared biochar material has a hierarchical porous structure, which significantly improves the selective adsorption performance of biochar for iodine. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of the ultra-high specific surface area coconut shell biochar prepared in Example 1;

[0023] Figure 2 This is the EDS image of the ultra-high specific surface area coconut shell biochar prepared in Example 1;

[0024] Figure 3The nitrogen adsorption and desorption isotherm curve of the ultra-high specific surface area coconut shell biochar prepared in Example 1;

[0025] Figure 4 This is the pore size distribution diagram of the ultra-high specific surface area coconut shell biochar prepared in Example 1;

[0026] Figure 5 The adsorption capacity of the ultra-high specific surface area coconut shell biochar prepared in Example 1 changes over time;

[0027] Figure 6 This is the SEM image of the coconut shell biochar prepared in Comparative Example 1;

[0028] Figure 7 This is the EDS image of the coconut shell biochar prepared in Comparative Example 1;

[0029] Figure 8 This is a nitrogen adsorption and desorption isotherm of the coconut shell biochar prepared in Comparative Example 1;

[0030] Fig. 9 This is the pore size distribution diagram of the coconut shell biochar prepared in Comparative Example 1;

[0031] Fig.10 This is the SEM image of the coconut shell biochar prepared in Comparative Example 2;

[0032] Fig.11 This is the EDS image of the coconut shell biochar prepared in Comparative Example 2;

[0033] Fig.12 This is a nitrogen adsorption and desorption isotherm of the coconut shell biochar prepared in Comparative Example 2;

[0034] Fig.13 This is the pore size distribution diagram of the coconut shell biochar prepared in Comparative Example 2;

[0035] Fig.14 This is the SEM image of the coconut shell biochar prepared in Comparative Example 3;

[0036] Fig.15 This is the EDS image of the coconut shell biochar prepared in Comparative Example 3;

[0037] Fig.16 This is a nitrogen adsorption and desorption isotherm of the coconut shell biochar prepared in Comparative Example 3;

[0038] Fig.17 This is the pore size distribution diagram of the coconut shell biochar prepared in Comparative Example 3. DETAILED DESCRIPTION

[0039] The method and features of the present invention are described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The coconut shells used in the following specific examples were purchased from Hainan, China, urea was purchased from Sinopharm Chemical Reagent Co., Ltd., potassium hydroxide was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., and elemental iodine was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The above drugs were used directly without further purification.

[0041] Example 1

[0042] A method for preparing ultra-high specific surface area coconut shell biochar, the specific steps are as follows:

[0043] (1) cleaning the dust and other impurities attached to the surface of the coconut shell with ultrapure water, drying it in an oven at 75° C. for 24 hours, crushing it, and passing it through a 100-mesh sieve to obtain coconut shell powder for later use;

[0044] (2) 10 g of coconut shell powder and 20 g of urea were added to a 100 mL polytetrafluoroethylene liner containing 60 mL of ultrapure water, and the mixture was fully mixed and placed in a stainless steel autoclave, and hydrothermally heated at 210° C. for 2 hours in a forced air drying oven, and then taken out after cooling; the hydrothermal product was obtained by drying in a forced air drying oven at 75° C. for 24 hours, and the product was set aside;

[0045] (3) The hydrothermal product was fully mixed with KOH at a mass ratio of 1:2.5 in a ball mill for 10 minutes, then transferred to an alumina boat and placed in a tube furnace. In a nitrogen environment of 80 mL / min, the tube furnace was heated to 950°C at a heating rate of 5°C / min and maintained for 2 hours, and a carbonized product was obtained after cooling.

[0046] (4) The carbonized product is rinsed with ultrapure water to remove excess alkali and salt until the pH value reaches about 7, and then the solid powder is filtered out and dried in a forced air drying oven at 75°C for 24 hours to obtain coconut shell biochar with ultra-high specific surface area.

[0047] The structural characteristics of the prepared ultra-high specific surface area coconut shell biochar were characterized and analyzed by SEM, EDS and BET.

[0048] like Figure 1 , 2 As shown in Figure 2, the microstructure and elemental composition (C, N, O) of the ultra-high specific surface area coconut shell biochar samples were analyzed using SEM and EDS. From the SEM image, it can be seen that the surface of the coconut shell biochar sample has an obvious pore structure and a smooth surface. The EDS image confirms that the coconut shell biochar sample contains the elements C, N and O, and they are evenly distributed.

[0049] like Figure 3 , 4 Shown are the nitrogen adsorption and desorption isotherms and pore size distribution diagrams of ultra-high specific surface area coconut shell biochar. The nitrogen adsorption and desorption isotherms of the biochar sample belong to the type IV isotherm model classified by IUPAC. In the low-pressure stage of P / P0<0.1, the rapid linear rise of the curve indicates that the biochar material is rich in micropores. When P / P0>0.1, the curve shows an obvious slope and hysteresis loop, indicating the presence of mesopores in the biochar. The ultra-high nitrogen adsorption and desorption capacity indicates that it has a rich pore structure. The pore size distribution diagram shows that the biochar sample is mainly composed of micropores and mesopores below 10nm. The ultra-high specific surface area coconut shell biochar prepared in Example 1 has a diameter of 2977.90m 2 / g ultra-high specific surface area, 2.19cm 3 / g total pore volume and 1.17cm 3 / g of micropore volume provided by the hierarchical porous structure.

[0050] Comparative Example 1

[0051] A coconut shell biochar was prepared according to the method of Example 1, except that urea was not used in step (2). The specific steps were as follows:

[0052] (1) cleaning the dust and other impurities attached to the surface of the coconut shell with ultrapure water, drying it in an oven at 75° C. for 24 hours, crushing it, and passing it through a 100-mesh sieve to obtain coconut shell powder for later use;

[0053] (2) 10 g of coconut shell powder was added to 100 mL of polytetrafluoroethylene liner containing 60 mL of ultrapure water, and after being fully mixed, the mixture was placed in a stainless steel autoclave, and hydrothermally heated at 210° C. for 2 hours in a forced air drying oven, and then taken out after cooling; the hydrothermal product was obtained after drying in a forced air drying oven at 75° C. for 24 hours, and the product was set aside;

[0054] (3) The hydrothermal product was fully mixed with KOH at a mass ratio of 1:2.5 in a ball mill for 10 minutes, then transferred to an alumina boat and placed in a tube furnace. In a nitrogen environment of 80 mL / min, the tube furnace was heated to 950°C at a heating rate of 5°C / min and maintained for 2 hours, and a carbonized product was obtained after cooling.

[0055] (4) The carbonized product is rinsed with ultrapure water to remove excess alkali and salt until the pH value reaches about 7, and the solid powder is filtered out and dried in a forced air drying oven at 75°C for 24 hours to obtain coconut shell biochar.

[0056] Characterization of the coconut shell biochar prepared in Comparative Example 1, such as Figure 6-9 As shown. Figure 6 , 7As shown, the microstructure and elemental composition (C, N, O) of the sample of comparative example 1 were analyzed using SEM and EDS. From the SEM image, it can be seen that the surface of the coconut shell biochar sample has an obvious pore structure and a regular flaky surface distribution. The EDS image confirms that the coconut shell biochar sample contains the elements C, N and O, and they are evenly distributed.

[0057] like Figure 8 , 9 The nitrogen adsorption-desorption isotherm and pore size distribution of the sample in comparative example 1 are shown in the figure. The nitrogen adsorption-desorption isotherm of the biochar sample belongs to the type IV isotherm model classified by IUPAC. The pore size distribution shows that the biochar sample is mainly composed of micropores and mesopores below 10 nm. The coconut shell biochar prepared in comparative example 1 has a pore size of 1845.97 nm. 2 / g specific surface area, 1.20cm 3 / g total pore volume and 0.76cm 3 / g of micropore volume.

[0058] Comparative Example 2

[0059] A coconut shell biochar was prepared according to the method of Example 1, except that KOH was not used in step (3). The specific steps were as follows:

[0060] (1) cleaning the dust and other impurities attached to the surface of the coconut shell with ultrapure water, drying it in an oven at 75° C. for 24 hours, crushing it, and passing it through a 100-mesh sieve to obtain coconut shell powder for later use;

[0061] (2) 10 g of coconut shell powder and 20 g of urea were added to a 100 mL polytetrafluoroethylene liner containing 60 mL of ultrapure water, and the mixture was fully mixed and placed in a stainless steel autoclave, and hydrothermally heated at 210° C. for 2 hours in a forced air drying oven, and then taken out after cooling; the hydrothermal product was obtained by drying in a forced air drying oven at 75° C. for 24 hours, and the product was set aside;

[0062] (3) The hydrothermal product was ball-milled in a ball mill for 10 minutes, then transferred to an alumina boat and placed in a tube furnace. In a nitrogen environment of 80 mL / min, the tube furnace was heated to 950°C at a heating rate of 5°C / min and maintained for 2 hours, and a carbonized product was obtained after cooling.

[0063] (4) The carbonized product is rinsed with ultrapure water to remove excess alkali and salt until the pH value reaches about 7, and the solid powder is filtered out and dried in a forced air drying oven at 75°C for 24 hours to obtain coconut shell biochar.

[0064] Characterization of the coconut shell biochar prepared in Comparative Example 2, such as Figure 10-13 As shown. Fig.10 , 11As shown, the microstructure and elemental composition (C, N, O) of the sample of Comparative Example 2 were analyzed using SEM and EDS. From the SEM image, it can be seen that the surface of the coconut shell biochar sample is rough and has small holes evenly distributed. The EDS image confirms that the coconut shell biochar sample contains the elements C, N and O, and they are evenly distributed.

[0065] like Fig.12 , 13 The following are the nitrogen adsorption and desorption isotherms and pore size distribution diagrams of the sample in Comparative Example 2. The pore size distribution diagram shows that the biochar sample is mainly composed of a small amount of micropores, mesopores and macropores. The coconut shell biochar prepared in Comparative Example 2 has a pore size of 34.20 m 2 / g specific surface area, 0.04cm 3 / g total pore volume and 0.01cm 3 / g of micropore volume.

[0066] Comparative Example 3

[0067] A coconut shell biochar was prepared by referring to the method of Example 1, except that urea was not used in step (2) and KOH was not used in step (3). The specific steps are as follows:

[0068] (1) cleaning the dust and other impurities attached to the surface of the coconut shell with ultrapure water, drying it in an oven at 75° C. for 24 hours, crushing it, and passing it through a 100-mesh sieve to obtain coconut shell powder for later use;

[0069] (2) 10 g of coconut shell powder was added to 100 mL of polytetrafluoroethylene liner containing 60 mL of ultrapure water, and after being fully mixed, the mixture was placed in a stainless steel autoclave, and hydrothermally heated at 210° C. for 2 hours in a forced air drying oven, and then taken out after cooling; the hydrothermal product was obtained after drying in a forced air drying oven at 75° C. for 24 hours, and the product was set aside;

[0070] (3) The hydrothermal product was ball-milled in a ball mill for 10 minutes, then transferred to an alumina boat and placed in a tube furnace. In a nitrogen environment of 80 mL / min, the tube furnace was heated to 950°C at a heating rate of 5°C / min and maintained for 2 hours, and a carbonized product was obtained after cooling.

[0071] (4) The carbonized product is rinsed with ultrapure water to remove excess alkali and salt until the pH value reaches about 7, and the solid powder is filtered out and dried in a forced air drying oven at 75°C for 24 hours to obtain coconut shell biochar.

[0072] Characterization of the coconut shell biochar prepared in Comparative Example 3, such as Figure 14-17 As shown. Fig.14 , 15As shown, the microstructure and elemental composition (C, N, O) of the sample of comparative example 3 were analyzed using SEM and EDS. From the SEM image, it can be seen that the coconut shell biochar sample has an irregular shape and a rough surface. The EDS image confirms that the coconut shell biochar sample contains the elements C, N and O, and they are evenly distributed.

[0073] like Fig.16 , 17 The following are the nitrogen adsorption and desorption isotherms and pore size distribution diagrams of the sample in comparative example 3. The pore size distribution diagram shows that the biochar sample is mainly composed of a small amount of micropores, mesopores and macropores. The coconut shell biochar prepared in comparative example 3 has a pore size of 24.96 m 2 / g specific surface area, 0.03cm 3 / g total pore volume and 0.01cm 3 / g of micropore volume.

[0074] The coconut shell biochar prepared in Example 1 and Comparative Examples 1 to 3 was tested for static adsorption of gaseous iodine and desorption rate at room temperature for 24 hours.

[0075] Test method and steps: 0.05 grams (m1) of prepared biomass carbon sample and excess elemental iodine (1 gram) were placed in different glass culture dishes, and then the two were placed together in a 250 ml sealed container. The container was then placed in an oven and heated to 75°C for 6 hours. After cooling, the sample weight (m2) was weighed and the capacity of biochar to adsorb gaseous iodine (q e mg / g). In order to evaluate the retention capacity of biochar samples for iodine, the biochar samples that were subjected to static adsorption of gaseous iodine were left to stand at room temperature for 24 hours and the sample mass (m3) was weighed. The mass was calculated by ((m2-m3 / m1)×1000) / q e )×100% to calculate the desorption rate (%).

[0076] Test results: Specific test results are as follows: Figure 5 As shown in Table 1, it is calculated that the adsorption amount of gaseous iodine by the ultra-high specific surface area coconut shell biochar prepared in Example 1 reaches 6635 mg / g at 75°C within 3 hours. The desorption rate at room temperature for 24 hours is 12.93%.

[0077] Table 1 Static adsorption of gaseous iodine by coconut shell biochar and 24-hour desorption rate at room temperature

[0078]

[0079]

[0080] The above test results show that the ultra-high specific surface area coconut shell biochar prepared in Example 1 can quickly adsorb gaseous iodine in a short time. On the one hand, it has an ultra-high specific surface area and a hierarchical porous structure, which not only provides an effective adsorption site for the biochar sample to adsorb gaseous iodine, but also allows the gaseous iodine to quickly enter the interior of the biochar sample. On the other hand, the rich nitrogen-containing functional groups and oxygen-containing functional groups on the surface of the biochar can effectively enhance the affinity of the biochar sample for gaseous iodine, thereby increasing the adsorption capacity. Therefore, the ultra-high specific surface area coconut shell biochar prepared in Implementation Method 1 can quickly adsorb gaseous iodine in a short time. In summary, the ultra-high specific surface area coconut shell biochar provided by the present invention effectively solves the problems of low adsorption capacity of existing carbon-based adsorbents, high cost of new materials, and potential toxicity, and efficiently treats radioactive gaseous iodine while realizing solid waste resource utilization.

[0081] The implementation of the present invention is not limited to the specific embodiments described. These embodiments are merely exemplary descriptions of the present invention, illustrating that the present invention can be implemented in different specific ways or forms without departing from its spirit or essential attributes. Therefore, the described embodiments should be regarded as illustrative rather than restrictive. The scope of protection of the present invention shall be based on the attached claims, and the scope of the present invention shall also cover any changes equivalent to the purpose and scope described in the claims.

Claims

1. A method for preparing ultra-high specific surface area coconut shell biochar, characterized in that: The following steps are involved: S1, washing, drying, crushing and sieving coconut shell to obtain coconut shell powder; S2, adding the coconut shell powder into a high pressure reactor and mixing with urea, drying after hydrothermal reaction to obtain a hydrothermal product for standby use; S3, mixing the hydrothermal product with KOH by ball milling, placing the mixture in a tube furnace, and carbonizing the mixture by heating under an inert atmosphere to obtain a carbonized product; S4, washing and drying the carbonized product to obtain coconut shell biochar with ultra-high specific surface area.

2. The method for preparing ultra-high specific surface area coconut shell biochar according to claim 1, characterized in that: Step S1 is to wash, dry, crush and sieve the coconut shell with 100-200 meshes.

3. The method for preparing ultra-high specific surface area coconut shell biochar according to claim 1, characterized in that: The mass ratio of the coconut shell powder to urea in step S2 is 1:1.5-3.

4. The method for preparing ultra-high specific surface area coconut shell biochar according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step S2 is 200-250° C., and the time of the hydrothermal reaction is 1.5 h to 3 h.

5. The method for preparing ultra-high specific surface area coconut shell biochar according to claim 1, characterized in that: The mass ratio of the hydrothermal product to KOH in step S3 is 1:2-3.

6. The method for preparing ultra-high specific surface area coconut shell biochar according to claim 1, characterized in that: In step S3, the carbonization temperature is 800-1000° C., and the carbonization time is 1.5 h-3 h.

7. The method for preparing ultra-high specific surface area coconut shell biochar according to claim 1, characterized in that: The heating rate in step S3 is 3-8°C / min.

8. An ultra-high specific surface area coconut shell biochar, characterized in that: Prepared by any one of the methods of claims 1 to 7, the coconut shell biochar has a specific surface area of ​​2900 to 3000 m 2 / g, total pore volume is 2.1~2.3cm 3 / g, micropore volume is 1.1~1.2cm 3 / g.

9. Use of the ultra-high specific surface area coconut shell biochar according to claim 8 in adsorbing gaseous iodine.